Gender-specific differences in COPD symptoms and their impact for the diagnosis of cardiac comorbidities - Trudzinski, Franziska; Kellerer, Christina; Jörres, Rudolf; Alter, Peter; Lutter, Johanna I.; Trinkmann, Frederik; Herth, Felix; Frankenberger, Marion; Watz, Henrik; Vogelmeier, Claus F.; Kauczor, Hans-Ulrich; Welte, Tobias; et al. (Clinical research in cardiology, 2021)
Background  In chronic obstructive pulmonary disease (COPD), gender-specific differences in the prevalence of symptoms and comorbidity are known. Research question  We studied whether the relationship between these characteristics depended on gender and carried diagnostic information regarding cardiac comorbidities. Study design and methods  The analysis was based on 2046 patients (GOLD grades 1-4, 795 women; 38.8%) from the COSYCONET COPD cohort. Assessments comprised the determination of clinical history, comorbidities, lung function, COPD Assessment Test (CAT) and modified Medical Research Council dyspnea scale (mMRC). Using multivariate regression analyses, gender-specific differences in the relationship between symptoms, single CAT items, comorbidities and functional alterations were determined. To reveal the relationship to cardiac disease (myocardial infarction, or heart failure, or coronary artery disease) logistic regression analysis was performed separately in men and women.
Gesehen am 17.04.2023